Battery

By adding the first solvent and the first additive with a dielectric constant ≤10 to the electrolyte of the lithium-ion battery, and adjusting the relationship between their mass proportion and the height of the separator glue layer, the electrolysis caused by the gummed separator blocking the pores is solved. It solves the problem of poor liquid infiltration and significantly improves the adhesion between the separator and the pole piece and the overall performance of the battery.

CN119315085APending Publication Date: 2025-01-14ZHEJIANG COSMX BATTERY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411362571.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

After hot pressing of existing lithium-ion batteries, the glue layer of the glue coating diaphragm blocks the pores of the membrane, resulting in poor electrolyte infiltration and increasing the battery's DC impedance (DCR) and lithium evolution problems.

Method used

Add a first solvent and a first additive with a dielectric constant ≤ 10 to the electrolyte of the battery, and adjust the relationship between their mass proportion in the electrolyte and the height of the separator glue layer to satisfy 3 ≤ (a + b )/(X/Y)≤60 to improve the adhesion between the separator and the pole piece and the wettability of the electrolyte.

Benefits of technology

It significantly improves the adhesion between the separator and the pole piece, solves the problem of poor electrolyte infiltration, reduces the DC resistance (DCR) of the battery, and improves the high-temperature performance and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315085A_ABST
    Figure CN119315085A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and provides a battery. The battery comprises a positive plate, a diaphragm and a negative plate which are laminated, the diaphragm comprises a first region, and the first region is a region, exceeding the positive plate, of the diaphragm in the width direction of the diaphragm; the diaphragm comprises a base film, and an adhesive layer is at least arranged on one side, close to the positive plate, of the base film; in the width direction of the diaphragm, the diaphragm further comprises a second region positioned between the positive plate and the negative plate; the protruding heights of the adhesive layers in the first area and the second area are marked as X and Y respectively; the electrolyte comprises a first solvent and a first additive of which the dielectric constants are both less than or equal to 10; based on the total mass of the electrolyte, the mass ratios of the first solvent and the first additive are respectively recorded as a and b; and (a + b) / (X / Y) is more than or equal to 3 and less than or equal to 60, so that the binding power of the diaphragm and a pole piece can be remarkably improved, and meanwhile, the infiltration problem caused by hole blockage of a diaphragm adhesive layer is effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a battery. Background Art

[0002] The bonding between the pole piece and the diaphragm plays an important role in the performance, safety and cycle life of lithium-ion batteries. In order to improve the bonding between the pole piece and the diaphragm, a glue-coated diaphragm is usually used in the prior art to improve the bonding. Although the glue-coated diaphragm can improve the bonding between the pole piece and the diaphragm, after the battery is hot-pressed, the glue layer in the glue-coated diaphragm will block the pores of the diaphragm, causing poor electrolyte infiltration, leading to problems such as increased battery DCR, and the reduction of the diaphragm porosity will also cause the problem of lithium precipitation. Summary of the invention

[0003] The object of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide a battery, wherein a first solvent and a first additive having a dielectric constant ≤10 are added to the electrolyte of the battery, and when the mass proportion of the first solvent in the electrolyte, the mass proportion of the first additive in the electrolyte, the height of the protrusion of the rubber layer of the diaphragm in the first area, and the height of the protrusion of the rubber layer in the second area meet a specific relationship, the bonding strength between the diaphragm and the electrode piece can be significantly improved, and at the same time, the wetting problem caused by the clogging of the diaphragm rubber layer is effectively solved.

[0004] In order to achieve the above object, the present invention provides a battery, the battery comprising a positive electrode sheet, a separator and a negative electrode sheet which are stacked; the separator comprises a first region, the first region being a region where the separator exceeds the positive electrode sheet along the width direction of the separator;

[0005] The diaphragm includes a base film, and the base film is provided with a glue layer at least on one side close to the positive electrode sheet; along the width direction of the diaphragm, the diaphragm also includes a second region located between the positive electrode sheet and the negative electrode sheet; the height of the protrusion of the glue layer in the first region is recorded as Xμm, and the height of the protrusion of the glue layer in the second region is recorded as Yμm;

[0006] The battery further includes an electrolyte, wherein the electrolyte includes a first solvent with a dielectric constant ≤10 and a first additive with a dielectric constant ≤10; based on the total mass of the electrolyte, the mass proportion of the first solvent is denoted as a, and the mass proportion of the first additive is denoted as b;

[0007] X, Y, a and b satisfy: 3≤(a+b) / (X / Y)≤60.

[0008] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0009] The battery provided by the present invention adds a first solvent with a dielectric constant ≤10 and a first additive with a dielectric constant ≤10 to the electrolyte. By adjusting the mass proportion (a) of the first solvent in the electrolyte, the mass proportion (b) of the first additive in the electrolyte, and the height (X) of the protrusion of the glue layer in the first area, and the height (Y) of the protrusion of the glue layer in the second area, when 3≤(a+b) / (X / Y)≤60, the bonding force between the diaphragm and the electrode sheet can be significantly improved, and the electrolyte infiltration problem caused by the pore blocking of the diaphragm glue layer can be effectively solved.

[0010] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 The figure shows the positional relationship between the diaphragm and the pole piece. Figure 1 The range indicated by A represents the second region of the diaphragm, and the range indicated by B represents the first region of the diaphragm.

[0012] Figure 2 The figure shows a schematic diagram of part of the diaphragm adhesive layer. Figure 2 The range indicated by X is the height of the protrusion of the glue layer in the first area, and the range indicated by Y is the height of the protrusion of the glue layer in the second area.

[0013] Figure 3 Shown is a schematic diagram of the positive electrode structure. Figure 3 The range shown by D is the width of the ceramic coating.

[0014] Figure numerals: 1-positive electrode sheet; 2-diaphragm; 3-negative electrode sheet; 4-glue layer in the second region; 5-glue layer in the first region; 6-positive electrode ear; 7-ceramic coating. DETAILED DESCRIPTION

[0015] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0016] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0017] In the present invention, the terms "battery", "lithium battery", "lithium-ion battery" and "lithium-ion secondary battery" all have the same meaning and refer to lithium-ion secondary batteries, which generally include an electrode assembly (such as a positive electrode sheet, a negative electrode sheet and a separator), a container (shell) for accommodating the electrode assembly, and an electrolyte.

[0018] In the present invention, the term "dielectric constant" refers to the ratio of the electric field reduction in the medium to the original external electric field (in a vacuum) when the dielectric generates induced charges and weakens the electric field when an external electric field is applied. The dielectric constant is an inherent property of a compound and can be obtained by consulting reference books, literature, etc. For example, the dielectric constant of an organic solvent can be queried from the Gaussian Manual or the Lang's Handbook of Chemistry. As an embodiment, the test method of the dielectric constant refers to the standard GB / T 31838.8-2024. As an embodiment, the test steps of the dielectric constant include: (1) preparing a parallel plate capacitor, in which a certain distance is set between two parallel plates; (2) injecting the organic solvent to be tested into the parallel plate capacitor to ensure that the solvent fills the capacitor; (3) connecting a power supply and changing the electric field strength by adjusting the voltage; (4) measuring and recording the capacitance value under different voltages, and the capacitance value is the dielectric constant.

[0019] The present invention provides a battery, the battery comprising a positive electrode sheet, a separator and a negative electrode sheet which are stacked; the separator comprises a first region, the first region being a region where the separator exceeds the positive electrode sheet along the width direction of the separator;

[0020] The diaphragm includes a base film, and the base film is provided with a glue layer at least on one side close to the positive electrode sheet; along the width direction of the diaphragm, the diaphragm also includes a second region located between the positive electrode sheet and the negative electrode sheet; the height of the protrusion of the glue layer in the first region is recorded as Xμm, and the height of the protrusion of the glue layer in the second region is recorded as Yμm;

[0021] The battery further includes an electrolyte, wherein the electrolyte includes a first solvent with a dielectric constant ≤10 and a first additive with a dielectric constant ≤10; based on the total mass of the electrolyte, the mass proportion of the first solvent is denoted as a, and the mass proportion of the first additive is denoted as b;

[0022] X, Y, a and b satisfy: 3≤(a+b) / (X / Y)≤60.

[0023] Exemplarily, the value of (a+b) / (X / Y) can be 3, 4, 5, 6, 8, 10, 15, 20, 25, 30, 35, 40, 45, 50, 52, 54, 56, 57, 58, 59, 60 or any point value in the range consisting of any two of the above point values.

[0024] Exemplarily, the values ​​of a, b, X, and Y can be set with reference to the conventional value ranges of a, b, X, and Y in the art. As long as the relationship between a, b, X, and Y satisfies 3≤(a+b) / (X / Y)≤60, it is within the protection scope of the present invention.

[0025] After hot pressing, the glue-coated diaphragm will block the pores of the base film, resulting in a decrease in the porosity of the entire diaphragm, which significantly reduces the wettability. In order to solve the problem of reduced wettability after hot pressing of the diaphragm, the present invention adds a first solvent with a dielectric constant ≤10 to the electrolyte. The lower the dielectric constant, the lower the viscosity of the first solvent. The first solvent can reduce the viscosity of the electrolyte and can be similarly soluble in the diaphragm glue layer, which can infiltrate faster, improve the overall wettability of the battery cell, and help reduce the DC resistance (DCR) of the battery cell. Adding a first additive with a dielectric constant ≤10 to the electrolyte as a wetting aid can play a synergistic role with the first solvent and further improve the wettability. Furthermore, when the mass proportion of the first solvent in the electrolyte (a), the mass proportion of the first additive in the electrolyte (b), the height of the rubber layer protrusion in the first region (X), and the height of the rubber layer protrusion in the second region (Y) satisfy 3≤(a+b) / (X / Y)≤60, the synergistic effect of the electrolyte and the diaphragm significantly improves the adhesion between the diaphragm and the electrode, and at the same time effectively solves the wetting problem caused by pore blockage. It can effectively avoid the problem of large diaphragm pore blockage area, insufficient electrolyte wettability, and high battery DCR when the value of (a+b) / (X / Y) is less than 3, and can also avoid the problem of degradation of battery high temperature performance when the value of (a+b) / (X / Y) is greater than 60.

[0026] It should be noted that when calculating the value of the formula (a+b) / (X / Y), a and b are substituted into the formula with the corresponding values ​​in percentage, and X and Y are substituted into the formula with the values ​​corresponding to the actual protrusion height of the adhesive layer. For example, when a=60%, b=1%, X=5μm, and Y=2μm, (a+b) / (X / Y)=(60+1) / (5 / 2)=24.4.

[0027] In some embodiments, Figure 1 As shown, the range shown in A represents the second area located in the diaphragm, and the range shown in B represents the first area of ​​the diaphragm, that is, the first area can be interpreted as the area where the diaphragm exceeds the positive electrode sheet.

[0028] In some embodiments, Figure 2 As shown, the thickness range indicated by X is the height of the protrusion of the glue layer 5 in the first area, and the thickness range indicated by Y is the height of the protrusion of the glue layer 4 in the second area.

[0029] In some embodiments, X, Y, a and b satisfy: 7.5≤(a+b) / (X / Y)≤37.5, and the value of (a+b) / (X / Y) can be, for example, 7.5, 8, 9, 10, 15, 20, 25, 30, 32, 34, 36, 37.5 or any point value in the range of any two of the above point values. When 7.5≤(a+b) / (X / Y)≤37.5 is satisfied, the wettability of the battery cell can be further improved, the migration speed of lithium ions can be increased, the DCR can be reduced, and the high temperature performance of the battery can be improved.

[0030] In some embodiments, the height X (μm) of the protrusion of the adhesive layer in the first region satisfies: 0.5≤X≤10; the height X of the protrusion of the adhesive layer in the first region can be, for example, 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm or any point value in the range of the above two point values. The height Y (μm) of the protrusion of the adhesive layer in the second region satisfies: 0.2≤Y≤5, and the height Y of the protrusion of the adhesive layer in the second region can be, for example, 0.2μm, 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm or any point value in the range of the above two point values. X / Y satisfies: 1.5≤X / Y≤10, and the value of X / Y can be, for example, 1.5, 2, 3, 4, 5, 6, 7, 8, 9, 10 or any point value in the range of the above two point values, preferably 2≤X / Y≤6. Due to the design that the size of the negative electrode sheet is slightly larger than that of the positive electrode sheet, after hot pressing, the first area of ​​the diaphragm will be subjected to less stress than the central area. Under the same hot pressing process, the height X of the protrusion of the glue layer in the first area of ​​the diaphragm is higher than the height Y of the protrusion of the glue layer in the second area, and as the pressure increases, the ratio of X / Y will gradually increase due to the difference in stress. Therefore, the size of the ratio of X / Y can indicate the degree of diffusion of the glue layer on the base film. The higher the ratio of X / Y, the smaller the pressing force on the glue layer, that is, the glue layer has not spread over a large area on the base film; the lower the height values ​​of X and Y, the more the glue layer has spread over a large area on the base film, which can easily lead to pore blockage in the diaphragm and reduce wettability. When 3≤(a+b) / (X / Y)≤60 is satisfied, further adjusting the value of X / Y to meet the above range can effectively avoid the problems of poor adhesion between the diaphragm and the electrode when X / Y<1.5 and large pore blockage area and poor wettability when X / Y>10, further improving battery performance and taking into account both high adhesion and high wettability.

[0031] In some embodiments, the sum of the mass fraction of the first solvent and the mass fraction of the first additive, a+b (%), recorded as the total mass fraction of the electrolyte, satisfies: 30≤a+b≤85, and a+b can be, for example, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, or any point value in the range of the above two point values, preferably 45≤a+b≤75. When 3≤(a+b) / (X / Y)≤60 is satisfied, and a+b is further adjusted to meet the above range, the problem of high viscosity of the electrolyte when a+b<30, which is not conducive to wetting, and high temperature performance degradation when a+b>85 can be effectively avoided, and the battery DCR is further reduced, and the wettability of the electrolyte and the high temperature performance of the battery are improved.

[0032] In some embodiments, based on the total mass fraction of the electrolyte, the mass proportion a(%) of the first solvent with a dielectric constant ≤10 satisfies: 10≤a≤80, where a can be, for example, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or any point value in the range composed of the above two point values, preferably 30≤a≤70. Since when a<10, the mass proportion of the first solvent is small, it cannot effectively improve the wettability and cannot reduce the battery DCR, while when a>80, the mass proportion of the first solvent is large, and it is easy to decompose and produce gas at high temperature, which will deteriorate the high temperature performance of the battery. Therefore, when 3≤(a+b) / (X / Y)≤60 is satisfied, further adjusting the mass proportion a(%) of the first solvent with a dielectric constant ≤10 to meet the above range can effectively improve the wettability, reduce the battery DCR, and optimize the high temperature performance of the battery.

[0033] In some embodiments, the mass proportion b (%) of the first additive with a dielectric constant ≤ 10 satisfies the following conditions: 0.5 ≤ b ≤ 10, and the mass proportion of the first additive can be, for example, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any point value in the range of the above two point values, preferably 1 ≤ b ≤ 5. When 3 ≤ (a + b) / (X / Y) ≤ 60 is satisfied, the mass proportion b (%) of the first additive is further adjusted to meet the above range, so that the first additive can better synergize with the first solvent, further improve the wetting performance, reduce the battery DCR, and improve the lithium ion transmission efficiency. It can avoid the poor wetting effect when the content of the first additive is too small (b < 0.5), the battery DCR is high, and the synergistic effect with the first solvent is not obvious; it can also avoid the problem that the defluorination reaction is easy to occur when the content of the first additive is too high (b > 10), hydrogen fluoride is generated, and the high temperature cycle performance of the battery is deteriorated.

[0034] After hot pressing of the coated diaphragm, the porosity of the diaphragm decreases, the channel for lithium ions to pass through the diaphragm becomes narrower, and the resistance to lithium ion transmission increases, resulting in a decrease in the amount of lithium embedded in the corresponding negative electrode. When the negative electrode cannot embed enough lithium ions, these lithium ions will precipitate on the surface of the negative electrode to form metallic lithium, affecting the battery performance. In order to further solve the problem of lithium precipitation in the battery after hot pressing of the coated diaphragm, the present invention further provides: the electrolyte also includes lithium bis(fluorosulfonyl)imide (LiFSI); based on the total mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide is recorded as c; the electrolyte also includes lithium hexafluorophosphate (LiPF6); based on the total mass of the electrolyte, the mass percentage of lithium hexafluorophosphate is recorded as d; c and d satisfy: 1.0≤c / 15+d / 12.5≤1.6. The value of c / 15+d / 12.5 can be, for example, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6 or any value in the range consisting of any two of the above values.

[0035] The present invention has found that when c / 12.5+d / 15.0<1.0, the lithium salt concentration is low, the conductivity is low, and the speed of lithium ion migration is slow, which cannot effectively solve the problem of lithium precipitation. When c / 15+d / 12.5>1.6, the viscosity of the electrolyte will increase, which is not conducive to wetting and will also hinder the migration of lithium ions. When 3≤(a+b) / (X / Y)≤60 is satisfied, and 1.0≤c / 15+d / 12.5≤1.6 is further satisfied, while improving the wettability and reducing the battery DCR, the addition of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate to the electrolyte can further reduce the viscosity of the electrolyte, improve the conductivity, and enhance the kinetic performance of the entire system, effectively solving the problem of lithium precipitation after hot pressing of the coated diaphragm.

[0036] In some embodiments, the mass percentage c of lithium bis(fluorosulfonyl)imide and the mass percentage d of lithium hexafluorophosphate satisfy: 0.1≤c / d≤3; the value of c / d can be, for example, 0.1, 0.5, 1, 1.5, 2, 2.5, 3 or any point value in the range of the above two point values. When 3≤(a+b) / (X / Y)≤60 and 1.0≤c / 15+d / 12.5≤1.6 are satisfied, the ratio of c / d is further adjusted to satisfy the above range, which can further avoid the problem that the viscosity of the electrolyte will not be significantly reduced due to c / d<0.1, that is, too little LiFSI and too much LiPF6, and the effect of improving the kinetics is poor, and c / d>3, that is, too much LiFSI and too little LiPF6, LiPF6 cannot effectively passivate the current collector, LiFSI will corrode the current collector, and the high temperature performance will be degraded.

[0037] In some embodiments, based on the total mass of the electrolyte, the mass percentage c (%) of lithium bis(fluorosulfonyl)imide satisfies: 1≤c≤20, and the mass percentage c of lithium bis(fluorosulfonyl)imide may be, for example, 1%, 3%, 5%, 7%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, or any point value in the range of any two of the above point values, preferably 3≤c≤10. When c satisfies 1≤c≤20, the viscosity of the electrolyte can be further reduced, the conductivity can be increased, the kinetic performance of the entire system can be improved, and the problem of lithium precipitation can be solved.

[0038] In some embodiments, based on the total mass of the electrolyte, the mass percentage content d (%) of lithium hexafluorophosphate satisfies: 1≤d≤20, and the mass percentage content d of lithium hexafluorophosphate, for example, can be 1%, 3%, 5%, 7%, 8%, 10%, 12%, 14%, 16%, 18%, 20% or any point value in the range of any two of the above point values, preferably 5≤d≤15. When d satisfies 1≤d≤20, the viscosity of the electrolyte can be further reduced, the conductivity can be increased, the kinetic performance of the entire system can be improved, and the problem of lithium precipitation can be solved.

[0039] In order to further dissociate lithium salts, provide more mobile lithium ions, and improve kinetics, the present invention further provides an electrolyte that also includes a second solvent with a dielectric constant ≥ 10; the mass proportion of the second solvent is recorded as m based on the total mass of the electrolyte; m and a satisfy: 0.25≤m / a<1.0, and the value of m / a can be, for example, 0.25, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.99 or any point value in the range of the above two point values. When m and a satisfy 0.25≤m / a<1.0, the problem of high temperature performance degradation of the battery cell caused by m / a<0.25 and the problem of high viscosity of the electrolyte being unfavorable for battery cell wetting when m / a>1.0 can be effectively avoided, and the high temperature performance and kinetic performance can be further improved.

[0040] In some embodiments, based on the total mass of the electrolyte, the mass proportion m (%) of the second solvent satisfies: 5≤m≤40, and the mass proportion of the second solvent can be, for example, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or any point value in the range of any two of the above point values, preferably 20≤m≤30. When m satisfies 5≤m≤40, the kinetic performance of the electrolyte can be further improved.

[0041] In some embodiments, the second solvent includes a cyclic carbonate organic substance with a dielectric constant ≥ 10. Exemplarily, the cyclic carbonate organic substance may be one or more of ethylene carbonate (EC, dielectric constant 89.6), fluoroethylene carbonate (FEC, dielectric constant 102), propylene carbonate (PC, dielectric constant 66.1), and butylene carbonate (BC, dielectric constant 55.9). Selecting the above cyclic carbonate organic substances can further improve the wettability of the electrolyte and optimize the high temperature performance of the battery.

[0042] In order to further improve the bonding strength between the electrode and the diaphragm, the present invention further provides: the surface of the base film facing the negative electrode is provided with a glue layer, the surface of the base film facing the positive electrode is provided with an inorganic coating, and the surface of the inorganic coating away from the base film is provided with a glue layer. When 3≤(a+b) / (X / Y)≤60 is satisfied, further performing the above arrangement can further improve the bonding strength between the electrode and the diaphragm while ensuring higher wettability and lower DCR.

[0043] In some embodiments, the glue layer includes a plurality of glue point areas arranged at intervals, and the average diameter of the glue point areas is 50μm-1000μm. The average diameter of the glue point areas can be, for example, 50μm, 100μm, 200μm, 300μm, 400μm, 500μm, 600μm, 700μm, 800μm, 900μm, 1000μm or any point value in the range composed of the above two point values. When the average diameter of the glue point area further meets the above range, it can effectively avoid the blockage of holes and the reduction of wettability due to large diffusion after hot pressing, and can also avoid the problem of low diffusion after hot pressing and weak bonding between the pole piece and the diaphragm due to the small average diameter of the glue point area, further improve the bonding force between the pole piece and the diaphragm, and improve the wettability of the electrolyte, reduce the battery DCR, and improve the battery performance.

[0044] In the present invention, "a plurality of glue spot areas arranged at intervals" can be interpreted as a plurality of identical or different glue spot areas uniformly distributed on the surface of the substrate at the same or different intervals. The identical or different glue spot areas can be reflected in the identical or different sizes of the glue spot areas, the identical or different shapes of the glue spot areas, the identical or different materials used in the glue spot areas, etc. Furthermore, on the entire surface of the glue layer, the glue spot areas can be arranged regularly or irregularly.

[0045] In the present invention, the specific shape of the glue spot area is not limited. Exemplarily, the specific shape of the glue spot area can be a regular shape or an irregular shape, for example, a circle, a triangle, a rectangle, a parallelogram, a regular polygon, etc., all of which are within the protection scope of the present invention.

[0046] In the present invention, when the glue spot area is non-circular, the diameter of the largest circumscribed circle is recorded as the average diameter of the glue spot area.

[0047] Exemplarily, the glue spot area can be formed by conventional spraying or other conventional means.

[0048] In some embodiments, the coverage area ratio of the glue layer on the inorganic coating or base film is 10%-60%, and the coverage area ratio can be, for example, 10%, 20%, 30%, 40%, 50%, 60%, or any point value in the range of the above two point values. When 3≤(a+b) / (X / Y)≤60 is satisfied, and the coverage area ratio of the glue layer on the inorganic coating or base film further satisfies the above range, the electrode and the diaphragm can maintain a high bonding force while improving the wettability of the electrolyte and reducing the battery DCR.

[0049] In some embodiments, the adhesive layer includes organic particles, and the organic particles include one or more of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyacrylic acid resin, polymethyl acrylate, butyl acrylate-acrylonitrile copolymer, polyacrylonitrile, ethylene-acrylic acid copolymer, and polyethyl acrylate. In some embodiments, the DV50 of the organic particles is 300μm-500μm, and the DV50 of the organic particles can be, for example, 300μm, 350μm, 400μm, 450μm, 500μm, or any point value in the range of the above two point values, and / or the DV90 is 100μm-800μm, and the DV90 of the organic particles can be, for example, 100μm, 200μm, 300μm, 400μm, 500μm, 600μm, 700μm, 800μm, 900μm, or any point value in the range of the above two point values. When the DV50 and / or DV90 of the organic particles further meet the above range, the problem of pore blockage caused by excessively large particle size of the organic particles and the loose bonding between the electrode and the diaphragm when the particle size is too small can be effectively avoided, and the adhesion between the electrode and the diaphragm can be further enhanced, thereby improving the wettability of the electrolyte.

[0050] In some embodiments, the first solvent includes a carbonate organic matter and / or a carboxylate organic matter with a dielectric constant ≤10; the first solvent includes one or more of dimethyl carbonate (dielectric constant 3.17), diethyl carbonate (dielectric constant 2.82), ethyl methyl carbonate (dielectric constant 2.9), ethyl acetate (dielectric constant 6.02), methyl acetate (dielectric constant 6.0), propyl acetate (dielectric constant 5.5), methyl propionate (dielectric constant 7.72), propyl formate (dielectric constant 7.16), ethyl formate (dielectric constant 8.5), and methyl formate (dielectric constant 2.9). When 3≤(a+b) / (X / Y)≤60 is satisfied, further selecting the carbonate organic matter and / or carboxylate organic matter with a dielectric constant ≤10 as the first solvent can further reduce the viscosity of the electrolyte, improve the kinetic performance, promote the transmission of lithium ions, improve the wettability and reduce the battery DCR.

[0051] In some embodiments, the first additive includes a fluorobenzene compound and / or a fluoroether compound.

[0052] In some embodiments, the fluorobenzene compound includes one or more of 1,3,5-trifluorobenzene, 1-fluorobenzene, 1,3-difluorobenzene, and 1,4-difluorobenzene.

[0053] In some embodiments, the fluoroether compound includes one or more of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, and 2,2,2-trifluoroethyl ether.

[0054] When 3≤(a+b) / (X / Y)≤60 is satisfied, further selecting the above compound as the first additive can form a better synergistic effect with the first solvent, improve the transmission efficiency of lithium ions, further reduce the viscosity of the electrolyte, be compatible with the glue layer, and accelerate the wetting speed.

[0055] In some embodiments, the electrolyte further includes a second additive, which includes at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl sulfate (DTD), methylene disulfonate (MMDS), succinonitrile (SN), adiponitrile (AND), glutaronitrile (GN), hexanetrinitrile (HTCN), ethylene glycol bis (propionitrile) ether (DENE), glycerol trinitrile (TCP), tetravinylsilane (TVS), tris (trimethylsilyl) borate (TMSB), hexamethyldisilazane (HMDS), triphenyl phosphite (TPPi), and pentafluoroethoxycyclotriphosphazene (PFPN).

[0056] In order to further improve the safety performance of the battery, the present invention further provides: the positive electrode sheet includes a positive electrode current collector and a positive electrode ear, at least one of the positive electrode ears is arranged on one side of the positive electrode current collector along the width direction of the positive electrode sheet, and the positive electrode sheet is provided with a ceramic coating on the side in the width direction. When the above arrangement is further performed, the generation of burrs piercing the diaphragm can be effectively reduced, and the risk of battery short circuit can be reduced.

[0057] In some embodiments, Figure 3 As shown, the positive electrode sheet includes a positive electrode collector (not shown in the drawings) and a positive electrode ear 6. The positive electrode ear 6 is arranged on one side of the positive electrode collector along the width direction of the positive electrode sheet. A ceramic coating 7 is arranged on one side of the positive electrode sheet in the width direction and close to the positive electrode ear 6. The range shown by D is the width of the ceramic coating 7.

[0058] In the present invention, a positive electrode active material layer is disposed on at least one side of the surface of the positive electrode current collector, and the ceramic coating is adjacent to or at least partially overlaps with the positive electrode active material layer.

[0059] In some embodiments, the width D of the ceramic coating is 1mm-5mm, and the width of the ceramic coating can be, for example, 1mm, 2mm, 3mm, 4mm, 5mm, or any point value in the range of the above two point values. When the width of the ceramic coating further meets the above range, it can avoid that the ceramic coating width is too small to completely cover the edge of the positive electrode sheet, which can easily cause a short circuit in the battery, and it can also avoid that the ceramic coating is too wide to occupy too much electrode position, increase the mass of inactive substances in the electrode sheet, and reduce the energy density of the battery.

[0060] In some embodiments, the ceramic coating includes ceramic particles. The ceramic particles are selected from at least one of inorganic metal oxides, inorganic metal nitrides and inorganic metal salts. Exemplarily, the inorganic metal oxides include boehmite, aluminum oxide, magnesium oxide, calcium oxide, titanium dioxide, silicon dioxide and zirconium dioxide. Exemplarily, the inorganic metal nitrides include tungsten nitride, silicon carbide, boron nitride, aluminum nitride, titanium nitride and magnesium nitride. Exemplarily, the inorganic metal salts include barium sulfate, calcium titanate and barium titanate.

[0061] In some embodiments, the DV50 of the ceramic particles is 0.05 μm-3 μm, and the value of DV50 can be, for example, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, or any point value in the range of the above two point values, and / or the DV90 is 0.3 μm-6 μm, and the value of DV90 can be, for example, 0.3 μm, 0.6 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, or any point value in the range of the above two point values. When the DV50 and / or DV90 of the ceramic particles further meet the above range, the ceramic particles can be more evenly distributed to form a smoother and denser ceramic coating, thereby reducing the risk of internal short circuit of the battery and improving the safety of the battery.

[0062] In some embodiments, the ceramic coating further includes a binder, and the binder may include at least one of polyvinylidene fluoride (PVDF), hexafluoroethylene, polytetrafluoroethylene, methacrylate, and styrene-butadiene rubber.

[0063] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0064] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0065] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0066] The batteries of the examples and comparative examples of the present invention were prepared according to the following preparation method, and the differences from Example 1-1 are shown below.

[0067] Example 1-1

[0068] (1) Preparation of electrolyte

[0069] In an argon glove box with water content <0.1ppm and oxygen content <0.1ppm,

[0070] Ethylene carbonate (EC, dielectric constant 89.6), ethyl methyl carbonate (EMC, dielectric constant 2.9) and dimethyl carbonate (DMC, dielectric constant 3.17) are mixed evenly, fully dried lithium hexafluorophosphate (LiPF6) is added thereto for stirring and dissolving, the mass of LiPF6 added is 9% of the total mass of the electrolyte, and then fully dried lithium bis(fluorosulfonyl)imide (LiFSI) is added thereto for stirring and dissolving, the mass of LiFSI added is 6% of the total mass of the electrolyte, 1% of 1-fluorobenzene (FB, dielectric constant 4.7) based on the total mass of the electrolyte is added, and 2.5% of vinylene carbonate (VC), 0.5% of fluoroethylene carbonate (FEC) and 0.5% of vinyl sulfate (DTD) based on the total mass of the electrolyte are added, stirred evenly, and the electrolyte is obtained after passing the physical property test. The first solvent EMC and DMC account for 60% of the total mass of the electrolyte, and the mass ratio of the two is 5:2.

[0071] (2) Preparation of positive electrode

[0072] Lithium iron phosphate LFP, polyvinylidene fluoride and acetylene black are put into a vacuum mixer in a mass ratio of 97:2:1, and N-methylpyrrolidone (NMP) is added. They are fully mixed under the action of the vacuum mixer until a uniform and fluid positive electrode slurry is formed, in which the solid content is 60wt%; the above positive electrode slurry is evenly coated on an aluminum foil with a thickness of 13μm, dried, rolled, slit, and punched to obtain a positive electrode sheet.

[0073] Ceramic slurry (ceramic particles of alumina and PVDF, DV50 of the ceramic particles is 2 μm, DV90 is 5 μm) is coated on the current collector close to the positive electrode ear side, and the width of the ceramic slurry coating is 1 to 3 mm.

[0074] (3) Preparation of negative electrode sheet

[0075] Graphite, styrene-butadiene rubber, sodium carboxymethyl cellulose and acetylene black are put into a vacuum mixer in a mass ratio of 96.5:1.5:1:1, deionized water is added, and the mixture is fully mixed under the action of the vacuum mixer to finally form a uniform and fluid negative electrode slurry with a solid content of 50wt%. The negative electrode slurry is evenly coated on a copper foil with a thickness of 4.5μm, dried, rolled and die-cut to obtain a negative electrode sheet.

[0076] (4) Preparation of batteries

[0077] The positive electrode sheet obtained in step (2), the negative electrode sheet obtained in step (3) and the separator (polyethylene film) with a PVDF coating layer (the DV50 of the organic particles is 400 μm and the DV90 is 500 μm) are combined by winding to obtain a bare cell, and then the bare cell is placed in an outer packaging foil; the electrolyte prepared in step (1) is injected into the dried qualified cell, and the battery is obtained through vacuum standing, vacuum packaging, aging, formation, secondary sealing, aging, sorting and other processes. The height X of the protrusion of the glue layer in the first area and the height Y of the protrusion of the glue layer in the second area are shown in Table 1.

[0078] (5) Test battery

[0079] (i) 25℃ 50% SOC DCR test

[0080] The batteries prepared in the examples and comparative examples were subjected to a 25°C high temperature cycle test. The specific test method is as follows:

[0081] Place the battery in a 25±1℃ environment and leave it for 120min; discharge it at a constant current of 0.5C to 2.5V and leave it for 30min; charge it at a constant current and constant voltage of 0.5C to 3.65V, with a cut-off current of 0.05C, and leave it for 30min; discharge it at a constant current of 0.5C to 2.5V, record the discharge capacity C0, leave it for 30min, charge it at a constant current and constant voltage of 1.0C to 3.65V, with a cut-off current of 0.05C, and leave it for 30min, discharge it at 1C to 50% SOC, i.e. C0×(1-50% SOC), leave it for 120min in a 25℃±1℃ environment, discharge it at 3C for 10S (sampling time 100ms), record the voltage at the end of the shelf as V1, the voltage at the end of the discharge as V2, and the actual discharge current as I, then the calculation formula of 25℃50% SOCDCR is:

[0082] DCR=(V1-V2) / I.

[0083] (ii) 45℃ high temperature cycle test

[0084] The batteries prepared in the examples and comparative examples were subjected to a 45°C high temperature cycle test. The specific test method is as follows:

[0085] Place the battery in a 45±1℃ environment, leave it for 180min, discharge it to 2.5V at 0.5C constant current, leave it for 30min, charge it to 3.65V at 0.5C constant current and constant voltage, cut off current 0.05C, leave it for 30min, discharge it to 2.5V at 0.5C constant current, record the discharge capacity C0, leave it for 30min, charge it to 3.65V at 1.0C0 constant current and constant voltage, cut off current 0.05C0, leave it for 30min, discharge it to 2.5V at 1.0C0 constant current, when the cycle reaches n times, record the last discharge capacity Cn, the capacity retention rate of the nth cycle is calculated as:

[0086] Capacity retention rate (%) = Cn / C0×100%.

[0087] (iii) Membrane air permeability

[0088] The batteries of the embodiment and the comparative example were disassembled, the diaphragms were taken out, and three diaphragms were cut at a longitudinal interval of 150 mm. If the diaphragm width was ≥100 mm, the sample size was 100 mm × 100 mm; if the diaphragm width was <100 mm, the sample size was 100 mm × diaphragm width. The diaphragm was placed in the test head of a permeability meter suitable for the test range for air permeability test, and the average value of the three test results was taken as the air permeability of the diaphragm. The higher the air permeability, the more serious the blockage of the diaphragm rubber layer.

[0089] Example 1-3, and Comparative Examples 1-3 are carried out with reference to Example 1-1, and the main differences are shown in Table 1. Among them, in Example 1, the mass proportion a of the first solvent in the electrolyte is changed; in Example 2, the mass proportion b of the first additive is changed. In Example 3, the height of the glue layer in the first area and the second area of ​​the diaphragm is changed by adjusting the thickness of the glue layer. In Comparative Example 1, the mass proportion of the first solvent is small and does not satisfy 3≤(a+b) / (X / Y)≤60. In Comparative Example 2, the first additive is not added. In Comparative Example 3, the mass proportion of the first solvent and the first additive is adjusted, resulting in not satisfying 3≤(a+b) / (X / Y)≤60.

[0090] Table 1

[0091]

[0092]

[0093] Note: “ / ” indicates that the first additive is not added.

[0094] As can be seen from Table 1, the present invention adds a first solvent with a dielectric constant ≤10 and a first additive with a dielectric constant ≤10 to the electrolyte, and adjusts the mass proportion of the first solvent in the electrolyte (a), the mass proportion of the first additive in the electrolyte (b), and the height of the rubber layer protrusion in the first region (X), and the height of the rubber layer protrusion in the second region (Y) when 3≤(a+b) / (X / Y)≤60. This can significantly improve the bonding force between the diaphragm and the electrode, and reduce the battery DCR at the same time, effectively solve the electrolyte infiltration problem caused by the pore blocking of the diaphragm rubber layer, and can also improve the high temperature cycle retention rate and increase the diaphragm permeability.

[0095] Examples Example 4-5 was carried out with reference to Example 1-1, and the main differences are shown in Table 2. In Example 4, the mass proportion c of LIFSI in the electrolyte was changed, wherein Example 4-4 was the electrolyte without LIFSI. In Example 5, the mass proportion d of LiPF6 in the electrolyte was changed.

[0096] Table 2

[0097]

[0098] Note: “ / ” indicates that the corresponding parameter is not tested.

[0099] It can be seen from Table 2 that when 3≤(a+b) / (X / Y)≤60 is satisfied, and 1.0≤c / 15+d / 12.5≤1.6 is further satisfied, the addition of lithium bis(fluorosulfonyl)imide (LIFSI) and lithium hexafluorophosphate (LiPF6) to the electrolyte can improve wettability and reduce battery DCR while further reducing electrolyte viscosity, improving conductivity, reducing the internal resistance of the battery, and improving cycle capacity retention.

[0100] Examples Example 6 was carried out in accordance with Example 1-1, and the main differences are shown in Table 3. In Example 6, the mass proportion m of the second solvent in the electrolyte was changed.

[0101] Table 3

[0102]

[0103] It can be seen from Table 3 that when 3≤(a+b) / (X / Y)≤60 is satisfied, and m and a further satisfy 0.25≤m / a<1.0, the high temperature performance and dynamic performance can be effectively improved and the internal resistance of the battery can be reduced.

[0104] Examples Example 7 was carried out in accordance with Example 1-1, and the main differences are shown in Table 4. In Example 7, the coverage area ratio of the adhesive layer was changed by adjusting the process of the adhesive layer.

[0105] Table 4

[0106]

[0107] It can be seen from Table 4 that when 3≤(a+b) / (X / Y)≤60 is satisfied and the coverage area ratio of the adhesive layer is further in the range of 10%-60%, it can ensure that the electrode and the diaphragm have a high adhesion while improving the wettability of the electrolyte and reducing the battery DCR.

[0108] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A battery, characterized in that: The battery comprises a positive electrode sheet, a separator and a negative electrode sheet which are stacked; the separator comprises a first region, and the first region is a region where the separator exceeds the positive electrode sheet along the width direction of the separator; The diaphragm includes a base film, and the base film is provided with a glue layer at least on one side close to the positive electrode sheet; along the width direction of the diaphragm, the diaphragm also includes a second region located between the positive electrode sheet and the negative electrode sheet; the height of the protrusion of the glue layer in the first region is recorded as Xμm, and the height of the protrusion of the glue layer in the second region is recorded as Yμm; The battery further includes an electrolyte, wherein the electrolyte includes a first solvent with a dielectric constant ≤10 and a first additive with a dielectric constant ≤10; based on the total mass of the electrolyte, the mass proportion of the first solvent is denoted as a, and the mass proportion of the first additive is denoted as b; X, Y, a and b satisfy: 3≤(a+b) / (X / Y)≤60.

2. The battery according to claim 1, characterized in that X, Y, a and b satisfy: 7.5≤(a+b) / (X / Y)≤37.5; Preferably, X / Y satisfies: 1.5≤X / Y≤10, more preferably 2≤X / Y≤6; Preferably, X satisfies: 0.5≤X≤10; and / or, Y satisfies: 0.2≤Y≤5.

3. The battery according to claim 1, characterized in that a+b satisfies: 30≤a+b≤85, preferably 45≤a+b≤75; Preferably, a satisfies: 10≤a≤80, more preferably 30≤a≤70; Preferably, b satisfies: 0.5≤b≤10, more preferably 1≤b≤5.

4. The battery according to claim 1, characterized in that The electrolyte further comprises lithium bis(fluorosulfonyl)imide; based on the total mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide is denoted as c; The electrolyte further comprises lithium hexafluorophosphate; the mass percentage of lithium hexafluorophosphate based on the total mass of the electrolyte is denoted as d; c and d satisfy: 1.0≤c / 15+d / 12.5≤1.

6.

5. The battery according to claim 4, characterized in that c and d satisfy: 0.1≤c / d≤3; Preferably, c satisfies: 1≤c≤20, more preferably 3≤c≤10; Preferably, d satisfies: 1≤d≤20, more preferably 5≤d≤15.

6. The battery according to any one of claims 1 to 5, characterized in that: The electrolyte further comprises a second solvent having a dielectric constant ≥ 10; the mass proportion of the second solvent is denoted as m based on the total mass of the electrolyte; m and a satisfy: 0.25≤m / a<1.0; Preferably, m satisfies: 5≤m≤40, more preferably 20≤m≤30; Preferably, the second solvent comprises a cyclic carbonate organic substance having a dielectric constant ≥10.

7. The battery according to any one of claims 1 to 5, characterized in that: The surface of the base film facing the negative electrode sheet is provided with a glue layer, the surface of the base film facing the positive electrode sheet is provided with an inorganic coating, and the surface of the inorganic coating away from the base film is provided with a glue layer; Preferably, the glue layer comprises a plurality of glue spot areas arranged at intervals, and the average diameter of the glue spot areas is 50 μm-1000 μm; Preferably, the coverage area ratio of the adhesive layer on the inorganic coating or base film is 10%-60%.

8. The battery according to claim 7, characterized in that The adhesive layer includes organic particles, and the organic particles include one or more of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyacrylic acid resin, polymethyl acrylate, butyl acrylate-acrylonitrile copolymer, polyacrylonitrile, ethylene-acrylic acid copolymer, and polyethyl acrylate; Preferably, the organic particles have a DV50 of 300 μm to 500 μm, and / or a DV90 of 100 μm to 800 μm.

9. The battery according to any one of claims 1 to 5, characterized in that: The first solvent comprises a carbonate organic substance and / or a carboxylate organic substance having a dielectric constant of ≤10; Preferably, the first solvent comprises one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, methyl acetate, propyl acetate, methyl propionate, propyl formate, ethyl formate, and methyl formate; Preferably, the first additive comprises a fluorobenzene compound and / or a fluoroether compound; Preferably, the fluorobenzene compound includes one or more of 1,3,5-trifluorobenzene, 1-fluorobenzene, 1,3-difluorobenzene, and 1,4-difluorobenzene; and / or the fluoroether compound includes one or more of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, and 2,2,2-trifluoroethyl ether.

10. The battery according to any one of claims 1 to 5, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode ear; at least one of the positive electrode ears is arranged on one side of the positive electrode current collector along the width direction of the positive electrode sheet, and a ceramic coating is arranged on the side edge of the positive electrode sheet in the width direction; Preferably, the width D of the ceramic coating is 1 mm-5 mm; Preferably, the ceramic coating comprises ceramic particles, and the DV50 of the ceramic particles is 0.05 μm-3 μm, and / or the DV90 of the ceramic particles is 0.3 μm-6 μm.

Citation Information

Cited By

  • Battery monomer, isolating membrane, battery and power utilization device

    CN119890559A